Early-life exposure to endocrine-disrupting chemicals and autistic traits in childhood and adolescence: a systematic review of epidemiological studies - Cunha, Yandra Giovanna de Oliveira; Amaral, Giovanna Cavalcanti Brito do; Felix, Alana Almeida; Blumberg, Bruce; Amato, Angelica Amorim (Frontiers in Endocrinology, 2023)
Aims Exposure to endocrine-disrupting chemicals (EDCs) during critical neurodevelopmental windows has been associated with the risk of autistic traits. This systematic review of epidemiological studies examined the association between maternal exposure to EDCs during pregnancy and the risk of autism spectrum disorder (ASD) in the offspring. Methods We searched PubMed, Web of Science, Scopus, and Google Scholar from inception to November 17, 2022, for studies investigating the association between prenatal exposure to EDCs and outcomes related to ASD. Two independent reviewers screened studies for eligibility, extracted data, and assessed the risk of bias. The review was registered in PROSPERO (CRD42023389386). Results We included 27 observational studies assessing prenatal exposure to phthalates (8 studies), polychlorinated biphenyls (8 studies), organophosphate pesticides (8 studies), phenols (7 studies), perfluoroalkyl substances (6 studies), organochlorine pesticides (5 studies), brominated flame retardants (3 studies), dioxins (1 study), and parabens (1 study). The number of examined children ranged from 77 to 1,556, the age at the assessment of autistic traits ranged from 3 to 14 years, and most studies assessed autistic traits using the Social Responsiveness Scale. All but one study was considered to have a low risk of bias. Overall, there was no association between maternal exposure to specific ECDs during pregnancy and the occurrence of autistic traits in offspring. Conclusions Findings from the epidemiological studies evaluated here do not support an association between prenatal exposure to ECDs and the likelihood of autistic traits in later in life. These findings should not be interpreted as definitive evidence of the absence of neurodevelopment effects of EDCs affecting ASD risk, given the limitations of current studies such as representative exposure assessment, small sample sizes, inadequacy to assess sexually dimorphic effects, or the effects of EDC mixtures. Future studies should carefully address these limitations.